2015
DOI: 10.1371/journal.pone.0135869
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Novel Low Cost Point of Care Tampon (POCkeT) Colposcope for Use in Resource Limited Settings

Abstract: IntroductionCurrent guidelines by WHO for cervical cancer screening in low- and middle-income countries involves visual inspection with acetic acid (VIA) of the cervix, followed by treatment during the same visit or a subsequent visit with cryotherapy if a suspicious lesion is found. Implementation of these guidelines is hampered by a lack of: trained health workers, reliable technology, and access to screening facilities. A low cost ultra-portable Point of Care Tampon based digital colposcope (POCkeT Colposco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 41 publications
0
57
0
Order By: Relevance
“…As a consequence of the prohibitive cost of colposcopes (US$10,000–$20,000), VIA is performed with a simple headlamp in most resource-limited settings 14. Nevertheless, the performance of naked eye VIA as a CC screening tool is far from optimal.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the prohibitive cost of colposcopes (US$10,000–$20,000), VIA is performed with a simple headlamp in most resource-limited settings 14. Nevertheless, the performance of naked eye VIA as a CC screening tool is far from optimal.…”
Section: Discussionmentioning
confidence: 99%
“…To enable use of our SDFM for clinical applications, we have developed a low-cost, portable “Pocket” microscope that is capable of imaging tissue vasculature at high resolution (47). This technology closely mimics our dark field microscope and is well suited for visualization of oral mucosa in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed comparison of both the POCkeT colposcope and standard-of-care colposcope systems has been previously described 12 . Briefly, the POCkeT colposcope is an investigational research device that is intra-vaginal, portable, and low cost (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…This provides comparable image quality while substantially decreasing cost through the use of a consumer grade light source and camera. The POCkeT colposcope is no more expensive than a SLR digital camera, but through bench testing we have demonstrated that it has comparable field of view, resolution and contrast compared to a standard-of-care colposcope 12 . Additionally, the POCkeT colposcope can be plugged into a cell phone, tablet or computer which provides power to the device; therefore, it does not directly require electricity from a wall plug or power adapter, which enables it to be used in low resource environments where a majority of the population may not have access to electricity 13 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation